Evaluating the performance of a coated tube adsorber for adsorption cooling - Dias, João M. S. (2022)
Adsorption cooling (AC) is an environmentally friendly alternative to conventional vapor compression cooling. In this paper, the performance of a coated tube adsorber suitable for AC systems is numerically evaluated. The developed adsorber uses silica gel-water as adsorbent-adsorbate working pair. A numerical model is used to analyze the influence of several governing parameters such as the evaporator, condenser and regeneration temperatures, cycle time, metal-adsorbent heat transfer coefficient, metal tube diameter, coating thickness and heat transfer fluid (HTF) velocity on the adsorber's performance. It is confirmed that increasing the evaporator temperature results on a performance increase whereas increasing the condenser temperature hindrances the system's performance. A regeneration temperature close to 70 oC results on the highest cooling coefficient of performance (COPc). The cycle time can be used as a system-controlling parameter to tune the COPc and the specific cooling power (SCP). The adsorber performs better when the regeneration time is 35% shorter than the adsorption time. The maximum COPc occurs when the metal-adsorbent heat transfer coefficient reaches values of 100 W.m-2.K-1. The SCP greatly increases until this coefficient reaches 350 W.m-2.K-1. The adsorbent coating thickness severely influences the performance of an AC system. It was found that the maximum COPc corresponds to a coating thickness of 1.75 mm and, the smaller the coating thickness the smaller the SCP. The metal tube's diameter and the HTF's velocity mainly influence the SCP since they have direct impact on the heat transfer rate exchanged between the HTF and the adsorbent material.